1,4-Bis(hexyloxy)benzene - Cheng, Hua (International Union of Crystallography, 2013)
The asymmetric unit of the title compound, C(18)H(30)O(2), contains one half-molecule situated on an inversion center. The alkyl chain adopts a fully extended all-trans conformation. The C atoms of the alkyl chain are almost coplanar, with a maximum deviation of 0.042 (6) Å from the mean plane,which is inclined to the central benzene ring by 6.80 (9)°. The crystal packing exhibits no short intermolecular contacts.